Cytotoxic Yohimbine‐Type Alkaloids from the Leaves of Rauvolfia vomitoria. Issue 12 (10th November 2020) - Zhan, Guanqun; Miao, Rongkun; Zhang, Fuxin; Wang, Xingbin; Zhang, Xinxin; Guo, Zengjun
Abstract: Two new yohimbine‐type monoterpene indole alkaloids, rauvines A and B, and six known derivatives were obtained from the leaves of R. vomitoria . The structures of rauvines A and B were determined by extensive spectroscopic analyses, 13 C‐NMR, and ECD calculations. This is the first time to determine the absolute configurations of yohimbine‐type N ‐oxides by quantum chemistry calculations ( 13 C‐NMR and ECD calculations). All the isolates were tested for their cytotoxicity against five human cancer cell lines. Rauvine B showed moderate cytotoxicity on human MCF‐7 breast, SWS80 colon, and A549 lung cancer cell lines with IC50 values of 25.5, 22.6, and 26.0 μM, respectively. Abstract :